2012
DOI: 10.1139/y2012-085
|View full text |Cite
|
Sign up to set email alerts
|

High cholesterol diet effects on ischemia–reperfusion injury of the heart

Abstract: Ischemic heart disease is the leading cause of morbi-mortality in developed countries. Both ischemia-reperfusion injury and mechanisms of cardioprotection have been studied for more than 50 years. It is known that the physiopathological mechanism of myocardial ischemia involves several factors that are closely related to its development, of which hypercholesterolemia is one of the main ones. Therefore, the objective of this review was to elucidate the effects of a high-cholesterol diet on normal ventricular fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
0
5
0
1
Order By: Relevance
“…Hyperlipidemias have significant cardiac consequences, since they are among the major risk factors of ischemic heart diseases [1]. The role of atherosclerosis is well studied in these pathologies; however, myocardial effects of hyperlipidemias that do not result in atherosclerosis, such as isolated hypercholesterolemia, is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlipidemias have significant cardiac consequences, since they are among the major risk factors of ischemic heart diseases [1]. The role of atherosclerosis is well studied in these pathologies; however, myocardial effects of hyperlipidemias that do not result in atherosclerosis, such as isolated hypercholesterolemia, is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were supported by Sun et al [58] in experiments on isolated cardiomyocytes subjected to hypoxia/reoxygenation. For several years, our laboratory has been studying the cardioprotection mechanisms against I/R injury [61][62][63][64][65][66]. In previous papers we showed that A1 adenosine receptors and K + ATP sensitive channels were involved in PostC cardioprotection mechanism [65].…”
Section: Ischemic Postconditioningmentioning
confidence: 99%
“…Serum lipids are related with the onset of several heart ailments. The cholesterol (CH), triglycerides (TG), low density lipoprotein (LDL) and high density lipoprotein (HDL) are more common in evaluating heart problems (Sultani et al, 2020): (D'Annunzio, Donato et al, 2012.…”
Section: Discussionmentioning
confidence: 99%